Tristram Shandy in the Age of Insurance. (29th May 2019) - Terry, Richard
Abstract: In 1762 the Equitable Life Assurance Society was founded, the first to calculate its premiums on actuarial principles. Its origin coincided with an increased appreciation of domestic risk and an expanding market for insurance products: the third quarter of the century saw a sharp spike in the issuing of fire insurance policies. In 1759 Sterne's Tristram Shandy introduced a character whose developmental years are almost uniquely beset by hazard and contingency. This article argues that Sterne's novel is constituted by an insurance 'mentality' in its appreciation of the inherent risks of life and how these might be calculated and mitigated.